DETERMINANTS OF NET INTEREST MARGINS IN INDONESIAN BANKING - Dadang Lesmana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to examine the effect of the business cycle and bank specific on net interest margin during the post-financial crisis 2007/2008. The research method uses the system generalized method moment (SYS-GMM) to analyze dynamic panel data bank in Indonesian period 2009-2015. The results showed that during the post-financial crisis, the effect business cycle especially the total bank loan (Credit) can be increased net interest margin in Indonesian banking but the Gross Domestic Product (GGDP) Growth is not significant. Second, bank specific on bank size (SIZE) and Capital Ratio (CAR) have a negative and significant effect on net interest margin. Meanwhile, Market Concentration (CR3) and Liquidity (LIQ) have a negative but not significant effect. Finally, Credit Quality has a positive impact on net interest margin but no significant.